Tolerance of rhizospheric and endophytic microbes to pesticide residues and their potential for rice growth - ERYNA ELFASARI RANGKUTI; ALINA AKHDIYA; ABDUL MUNIF; ISKANDAR ZULKARNAEN SIREGAR; SYAIFUL ANWAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rangkuti EE, Akhdiya A, Munif A, Siregar IZ, Anwar S. 2025. Tolerance of rhizospheric and endophytic microbes to pesticide residues and their potential for rice growth. Biodiversitas 26: 5267-5276. Rhizospheric and endophytic bacteria are recognized for their ability to enhance plant growth by producing hormones and acting as biocontrol agents. Therefore, this study aimed to identify potential rhizosphere and endophytic bacteria tolerant to three pesticide-active substances. Based on the antagonistic activity against Rhizoctonia solani, Bacillus sp. and Bacillus siamensis isolates achieved the highest inhibitory activities of 81.13 % and 78.55 %, respectively. Bacillus sp., B. siamensis, Acinetobacter radioresistens, and Providencia vermicola were able to solubilize phosphate. Production of Indole-3-Acetic Acid (IAA) was confirmed in Bacillus sp., Bacillus toyonensis, and Acinetobacter radioresistens, and all isolates also possessed the ability to fix nitrogen (N). Based on these parameters, Bacillus sp. and B. siamensis were selected for further analysis. The results showed that Bacillus sp. isolates supported rice seed tolerance to herbicides and insecticides in the range of 5-10 ppm and improved growth in the presence of difenoconazole and glyphosate at 10 ppm. Meanwhile, B. siamensis was tolerant to fungicides in the 5-10 ppm range. None of the selected isolates showed reduced growth after 24 h of incubation in the tolerance test for pesticide contamination. Observably, Bacillus sp. isolate treated with fipronil (5 ppm) was better than the control. It also matched the performance of the control treated with difenoconazole at 5 ppm. These suggested that the selected isolates improved rice growth and tolerance to the active ingredients of the pesticides, contributing to sustainable cultivation practices.